3D Petrophysical Model for Mansouriya Gas Field/Jeribe Formation by using Petrel - Azeez, Hasan Saleh; Al-Dabaj, Dr. Abdul Aali; Lazim, Dr.Samaher Abdil-Rasool (Journal of Petroleum Research and Studies, 2020)
Mansuriya Gas field is an elongated anticlinal structure aligned from NW to SE about 25 km long and 5-6 km wide. The Jeribe formation considered the main reservoir, contains gas condensate fluid, has a uniform thickness about 60 m. The reservoir is significantly overpressured. In this study, the 3D geological model for Jeribe Formation in Mansuriya Gas Field is setup by using Petrel. Jeribe Formation represents the most important reservoir in Mansuriya Gas Field. Four vertical wells (Mn-1, Mn-2, Mn-3 and Mn-4) were drilled in Mansuriya Gas Field and used to set-up water saturation and porosity models represented by a 3D static geological model in three dimensions. The main reservoir, Jeribe Formation carbonate, is subdivided into 8 zones namely J1 to J8, according mainly to porosity log (RHOB and NPHI) trend, DT trend and saturation trend. Petrophysical model (porosity and water saturation) for Jeribe Formation was set-up from values of porosity and water saturation using Sequential Gaussian Simulation algorithm. According to data analyses and the results from modeling the units (J1, J3, J4, J5, J6 and J8) are considered as high-quality reservoir units due to the high PHIE, low water saturation and no shale content. Units (J2 and J7) are considered as non-pay units because of very high-water saturation. Cross sections of petrophysical model were conducted to show the vertical and horizontal distribution of porosity and water saturation between wells in the field.